2017
DOI: 10.1080/13625187.2017.1357808
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of contraceptive injections at the community pharmacy

Abstract: Delivery of the subcutaneous contraceptive injectable from a community pharmacy may be feasible but availability of sufficient numbers of pharmacists trained in this technique is necessary for a robust model of service delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 212 publications
(305 reference statements)
0
13
0
1
Order By: Relevance
“…They perceived the main benefit to GPs of extended pharmacy services was to reduce workload pressures (Agomo, Ogunleye, & Portlock, 2016a;Atkins et al, 2016;Morecroft et al, 2015;Pumtong et al, 2008), freeing up GPs time to deal with more urgent matters (Heller, Johnstone, & Cameron, 2017;Morecroft et al, 2015). In terms of their own benefit, most pharmacists viewed these services as an opportunity for role expansion/professional development, improving their relationships with patients (Butt & Ream, 2016;Campion et al, 2007;Latif et al, 2016;Paudyal et al, 2010;Pumtong et al, 2008;Urwin et al, 2016) and GPs (Agomo et al, 2016a;Pumtong et al, 2008).…”
Section: Perceived Value Of Services/rolesmentioning
confidence: 99%
“…They perceived the main benefit to GPs of extended pharmacy services was to reduce workload pressures (Agomo, Ogunleye, & Portlock, 2016a;Atkins et al, 2016;Morecroft et al, 2015;Pumtong et al, 2008), freeing up GPs time to deal with more urgent matters (Heller, Johnstone, & Cameron, 2017;Morecroft et al, 2015). In terms of their own benefit, most pharmacists viewed these services as an opportunity for role expansion/professional development, improving their relationships with patients (Butt & Ream, 2016;Campion et al, 2007;Latif et al, 2016;Paudyal et al, 2010;Pumtong et al, 2008;Urwin et al, 2016) and GPs (Agomo et al, 2016a;Pumtong et al, 2008).…”
Section: Perceived Value Of Services/rolesmentioning
confidence: 99%
“…Users found pharmacies convenient, easy and quick to access and use. They liked that compared to other providers, no appointments needed to be organised (25)(26)(27)(28)(29)(30)(31)(32)(33). However, a barrier to service delivery experienced by some users was that trained staff were not always available to provide the service (32).…”
Section: Suitabilitymentioning
confidence: 99%
“…With the exception of some younger individuals, pharmacy users generally had a positive counselling experience, felt comfortable discussing sexual health (26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and found that appropriate advice was provided (26)(27)(28)30,31,(33)(34)(35). However, in two quantitative studies, pharmacy users found counselling on EC less informative and satisfactory compared to users of other sexual health providers (25,34,35): Whereas 95% of users of clinical services (78/83) agreed that adequate advice on EC was provided, fewer pharmacy users (82%; 41/50) did so (25).…”
Section: Counsellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Wydaje się, że wydzielenie przestrzeni konsultacyjnej, przynajmniej częściowo mogłoby ułatwić farmaceutom dyskutowane zadania [9]. Potrzeba wydzielenia pomieszczenia/boksu w aptece nabiera szczególnego znaczenia w kontekście innych działań podejmowanych przez farmaceutów na świecie w ramach promocji zdrowia seksualnego -wymienić tu można dla przykładu podawanie kontynuacji zastrzyku antykoncepcyjnego (Depo-Provera ® ) [10].…”
Section: Zdrowie Seksualne I Reprodukcyjneunclassified